Coping with the dark sides of online learning. A case of tourism students - Marcin Olszewski (Studia Periegetica, 2022)
Online learning is nothing new, but during the COVID-19 pandemic, this form of education has become the preferred and sometimes the only option available as a result of social distancing and nationwide lockdowns. This unprecedented change has triggered a number of previously unknown problems and has forced students to find ways of coping with them. This study investigates the dark sides of online education and coping strategies developed by students by drawing on insights from coping theories to explain students’ adaptive responses. The study is based on qualitative data collected in an online survey of 27 students of tourism from a public university in Poland. The most frequent problem reported by the respondents were technical issues occurring during classes, followed by the lack of motivation and commitment, difficulties with sustained attention and the lack of contact with peers. The majority of students coped with stress caused by the negative aspects of technology in online education by engaging in physical activity. The findings of the study could contribute to guiding the direction for effective and student-friendly adoption of online education.